2013
DOI: 10.1007/s10853-013-7453-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable electrospun PLLA/chitosan membrane as guided tissue regeneration membrane for treating periodontitis

Abstract: This paper explores the application potential of a biodegradable PLLA/chitosan electrospun composite membrane for guided periodontal tissue regeneration which in addition serves as a fibroblast barrier. Electrospinning was applied to fabricate the PLLA membrane and aminolysis method was applied to graft chitosan on its surface. The morphology of the PLLA/chitosan membrane was observed by SEM. The surface chemical composition was analyzed by XPS. The appearance of N 1s peak in XPS demonstrated the successful gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…In our previous study, a PLA/chitosan membrane has been successfully fabricated and showed great potential to avoid fibroblast invasion which was an unfavorable side effect in periodontal regeneration [7]. Base on that research, we continue to improve the design to make it more suitable for the regeneration of both alveolar bone and gingiva tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, a PLA/chitosan membrane has been successfully fabricated and showed great potential to avoid fibroblast invasion which was an unfavorable side effect in periodontal regeneration [7]. Base on that research, we continue to improve the design to make it more suitable for the regeneration of both alveolar bone and gingiva tissue.…”
Section: Discussionmentioning
confidence: 99%
“…PLA is safe, while its degradation rate is relatively slow (more than 6 months) depending on the average molecular weight. However, according to our previous research, if mixed with other chemical, it was possible to adjust the degradation time to desired point by adjusting the proportion of the components in the mixture [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research has also shown it to have some efficacy with tissue regeneration in the setting of periodontitis [64]. To improve the bioactivity of chitosan, research has looked to modify the polymer through copolymerization.…”
Section: Natural Polymersmentioning
confidence: 99%
“…Poly(lactic-co-glycolic acid)/collagen/hydroxyapatite Non Comercial [70] Poly(l-lactic acid)/chitosan Non Comercial [71] Polycaprolactone/ starch / calcium / silicon Non Comercial [43] Polycaprolactone/ calcium carbonate Non Comercial [50] Poly(e-caprolactone)/silica Non Comercial [42] Poly(trimethylene carbonate) Non Comercial [44] Poly(lactic-co-glycolic acid) BioMesh Samyang's, Daejeon, Korea [72] Poly(DL-lactic acid)/ Bioglass ® Non Comercial [49] Poly(DL-lactic acid) EpiGuide ® THM Biochemical, Inc., Duluth,MN,USA [73] Poly(DL-lactide-co-glycolide) Resolut ® Gore-Tex Regenerative Material; W. L. Gore & Associates, Flagstaff, AZ, USA [27] Polylactic acid Guidor Matrix Barrier ® Guidor AB. Huddinge, Sweden [65] Other synthetic polymers, such as polycaprolactone or poly (trimethylene carbonate) were studied for GTR.…”
Section: Synthetic Origin Membranesmentioning
confidence: 99%